Fabrication of metal nanopatterns for organic field effect transistor electrodes by cracking and transfer printing. (16th February 2018) - Wang, Xiaonan; Fu, Tingting; Wang, Zhe
Abstract: In this paper, we demonstrate a novel method for fabricating metal nanopatterns using cracking to address the limitations of traditional techniques. Parallel crack arrays were created in a polydimethylsiloxane (PDMS) mold using a combination of surface modification and control of strain fields. The elastic PDMS containing the crack arrays was subsequently used as a stamp to prepare nanoscale metal patterns on a substrate by transfer printing. To illustrate the functionality of this technique, we employed the metal patterns as the source and drain contacts of an organic field effect transistor. Using this approach, we fabricated transistors with channel lengths ranging from 70–600 nm. The performance of these devices when the channel length was reduced was studied. The drive current density increases as expected, indicating the creation of operational transistors with recognizable properties.